Perawatan Fresh Water Cooler Pada Mesin Induk Type Mitshubishi 4D 30 Fe Kapal Motor Penumpang Trisila Bhakti I - Rahim Subliansyah Putra; Arif Rakhman Suharso; Yulius Oscar (PPPM Polimarin, 2023)
The diesel engine is an internal combustion engine that produces heat energy and motion energy. Overheating the engine can cause damage. To prevent excessive heat in a diesel engine, cooling is needed, the component that acts as a coolant is a fresh water cooler. normal temperature condition of fresh water cooler is 65ᵒC. The purpose of this study was to find out how maintenance actions are carried out on the fresh water cooler of the main driving diesel engine cooling system if overheating occurs. The research method used in this research is descriptive research, namely research that aims to describe and describe the object under study. Observation of temperature on the control panel of the main engine from the observation of temperature control there was an increase in temperature of 85ᵒC and an alarm sounded so that a fresh water cooler was checked and repaired. This is thought to be caused by the presence of dirt and corrosion in the cooling holes. And at that time, the pressure of the sea water cooling pump decreased from 3.0 kg/cm2 to 2.0 kg/cm2. The research results obtained a blockage in the sea water filter section so it needs to be cleaned and checked so that the incident does not happen again. The conclusion of this research is that the fresh water cooler maintenance on the ship has been going well, carried out according to the machine instructions work instructions, according to schedule. The results of the maintenance are that the engine temperature returns as expected.